Capability of boiling water of bay leaf (Eugenia polyantha W) for reducing Streptococcus sp. colony - Agustin Wulan; Agus Sumono (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2009)
Mouth is one of our body parts that have a lot of micro-organisms. The population of micro organism in mouth is higher than the other part of our body. Streptococcus mutant is a cariogenic bacterium that has the capability to produce polysaccharide and initiate the process of carries. There are many ways for preventing dental carries, one of them is using of antiseptic mouth washes. chlorhexidine is one of the most effective mouth washes used to prevent the dental carries and the plaque formation. Unfortunately, only some people who has easy access to the drugs store to get this medicine. So they use herbal that has capability for mouth washes, one of that herbal is bay leaf (Eugenia polyantha W). Aim of this study was to know capability of bay leaf (Eugenia polyantha W) as mouth washes for reducing Streptococcus sp colony.Saliva samples are taken from 50 patients that come in Dental Hospital Faculty of Dentistry Jember University. 50 patients are divided in 5 groups. Patients were instructed to rinse by 50 %, 75 %, 100 % boiling water of bay leaf, 0.2 % chlorhexidine and aquadest. Then, saliva was inoculates in TSA medium and incubated for 24 hours, before bacteria colony counting.Result of anova test showed there was significant different of amount of Sterptococcus colony in saliva patient that are rinsed by 50 %, 75 %, 100 % boiling water of bay leaf, 0.2 % chlorhexidine and aquadest (p < 0.05). Result of LSD test show there where significant different in each groups (p < 0.05). The conclusion of this study was boiling water of bay leaf can reduce Streptococcus sp colony.Key words : bay leaf, mouth washes, bacterial colony.